2013
DOI: 10.1007/s00268-013-1954-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Hepatic and Pulmonary Metastasectomies Compared With Pulmonary Metastasectomy Alone in Patients With Colorectal Cancer Metastasis to Liver and Lungs

Abstract: Resection of pulmonary colorectal metastases may increase survival. However, the combination of liver and lung metastasectomies had a worse prognosis than pulmonary metastasectomy alone. In selected patients, combined liver and lung metastasectomy can be beneficial and result in acceptable DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 56 publications
1
28
1
1
Order By: Relevance
“…Therefore, carefully selected patients with synchronous metastases confined to the lung and liver can be candidates for radical surgery. Previous studies projected a 5-year survival of 25-74% following liver and lung resections for metastases from CRC in selected patients (17,(20)(21)(22)(23), which were similar to the surgical outcomes for CRC with liver-only or lung-only metastases. Consistent with previous findings (18,19), patients who underwent curative resections achieved a markedly longer OS than those who underwent palliative therapies in the present study (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, carefully selected patients with synchronous metastases confined to the lung and liver can be candidates for radical surgery. Previous studies projected a 5-year survival of 25-74% following liver and lung resections for metastases from CRC in selected patients (17,(20)(21)(22)(23), which were similar to the surgical outcomes for CRC with liver-only or lung-only metastases. Consistent with previous findings (18,19), patients who underwent curative resections achieved a markedly longer OS than those who underwent palliative therapies in the present study (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…The 3-year survival rate after pulmonary metastasectomy ranged from 53 to 80% and the 5-year survival rate was reported to be 37-68% (12)(13)(14)(15)(16)(17). However, subjects in these studies had synchronous and metachronous lung metastases (12,13,15).…”
Section: Discussionmentioning
confidence: 93%
“…In a retrospective study, Hattori et al evaluated outcomes after pulmonary resection of colorectal metastases in patients with or without a curative hepatic metastasectomy. The 5-year OS of the lung metastasectomy group was significantly better than that of the liver and lung metastasectomy group 6. Similarly, a Japanese study showed that surgical resection offers a chance to prolong survival in colorectal cancer patients with resectable pulmonary metastases 7…”
Section: Discussionmentioning
confidence: 96%
“…Полное циторедуктивное хирургическое лечение -единственный метод, дающий пациентам шанс на долгосрочную выживаемость. Доля таких больных в нашей работе невелика, а актуариальная 3-летняя ОВ составляет 60 % по сравнению с 37-68 % по данным зарубежных публикаций [15,[18][19][20][21][22].…”
Section: Discussionunclassified